Air‐Droplet Interfaces: Interfacial Self‐Assembly of Colloidal Nanoparticles in Dual‐Droplet Inkjet Printing (Adv. Mater. Interfaces 10/2018). Issue 10 (22nd May 2018) - Al‐Milaji, Karam Nashwan; Secondo, Ray Richard; Ng, Tse Nga; Kinsey, Nathaniel; Zhao, Hong
Abstract : A nearly monolayer, closely‐packed nanoparticle deposition is demonstrated by a dual‐droplet inkjet printing process. The colloidal nanoparticles in a wetting droplet spread on a supporting droplet and self‐assemble into a monolayer film at the interface. Upon solvent evaporation, the nearly monolayer deposition forms on the substrate, which exhibits structural reflection colors. The self‐assembly mechanism during printing enables potential applications in printed optical and electrical devices. More details can be found in article number1701561 by Hong Zhao and co‐workers.